Fabrication and Physiochemical Properties of Alginate and Honey Biofilm for Wound Healing Applications - Yusop, Fatin Amirah; Mohamad Hasshim Mohd. Sabirin; Idris, Maizlinda Izwana (Research Progress in Mechanical and Manufacturing Engineering, 2024)
This research about the fabrication and characterization of alginate and honey biofilms, exploring their potential applications in wound healing. Alginate wound dressings, derived from brown seaweed, are recognized for their notable features, such as high permeability, biocompatibility, moisture retention, and gel-forming capabilities. This research investigates the collaborative properties of alginate and manuka honey, a natural wound-healing agent renowned for its antimicrobial, anti-inflammatory, and antioxidant effects. The experiment uses the solution casting technique to create biofilms with varied alginate (1 gram to 2 grams) and honey concentrations (0 ml to 30 ml) crosslinked with 0.1% calcium chloride. Results acquired through Scanning Electron Microscope (SEM), contact angle measurements, Fourier Transform Infrared Spectroscopy (FTIR), and Atomic Force Microscope (AFM) illuminate how honey influences the biofilm’s microstructure, surface roughness, and hydrophilicity. Elevated honey concentrations contribute to increased thickness, roughness, and porosity, impacting the overall structural integrity. The contact angle results affirm the hydrophilic nature of the biofilm surfaces, which is crucial for wound healing by enhancing moisture retention. SEM images vividly portray irregularities, including pores and rough surfaces, attributed to uneven drying and solidification processes. AFM analysis corroborates these findings by revealing higher surface roughness in the 2% w/v biofilm, aligning with SEM observations. FTIR spectra provide nuanced insights into the chemical composition of honey and its intricate interaction with alginate. The study posits that alginate and honey biofilms exhibit diverse compositions, showcasing their versatility for customized wound care applications. The acquired insights significantly contribute to comprehending biofilm development and its potential implications in wound healing. The confirmed hydrophilicity of these biofilms, coupled with their varied compositions, prompts further exploration of their behavior in interaction with host tissues. Ultimately, this research underscores the promising role of alginate and honey biofilms in advancing wound care strategies, providing valuable insights for developing effective wound healing protocols.